1998
DOI: 10.1021/jp981039h
|View full text |Cite
|
Sign up to set email alerts
|

Deviations from the Normal Time Regime of Single-File Diffusion

Abstract: Deviations from the ideal single-file behavior in actual systems, such as zeolitic host-guest systems with a one-dimensional channel structure, may occur if (i) there is a possibility of mutual passages of the diffusants and (ii) the influence of the file boundary on the movement of the diffusants cannot be neglected. The conditions under which such deviations may become relevant are investigated both by analytical methods and molecular dynamics simulations. The consequences of these deviations for experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
164
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(171 citation statements)
references
References 19 publications
7
164
0
Order By: Relevance
“…These effects make it very difficult to determine single-file diffusion in experiments. 388 For example, for methane and ethane in AFI (AlPO 4 -5), some groups observe single-file diffusion 384,385 while others conclude normal diffusion. 387 Simulations have been used to investigate these controversies in detail.…”
Section: Single-file Diffusionmentioning
confidence: 99%
“…These effects make it very difficult to determine single-file diffusion in experiments. 388 For example, for methane and ethane in AFI (AlPO 4 -5), some groups observe single-file diffusion 384,385 while others conclude normal diffusion. 387 Simulations have been used to investigate these controversies in detail.…”
Section: Single-file Diffusionmentioning
confidence: 99%
“…where the diffusion coefficient has been replaced by a mobility factor, F x [6,7]. Single file diffusion occurs in a variety of natural and engineered systems, including ion and water transport through biological membranes [8][9][10][11], diffusion in molecular sieves such as zeolites [12][13][14], carbon nanotubes [15], * richard.bowles@usask.ca or metal organic frameworks [16,17], and charge-carrier diffusion in one dimensional channels [18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MD studies 52 have suggested that when molecules have the ability to pass each other in the nanopore, small changes in the system can have a significant effect on the results, which further complicates the characterization of transition-mode diffusion. Temperature also has been shown to play a role in determining the diffusion mode, 53 where higher temperatures allow molecules that might normally not be able to, to squeeze past one another.…”
mentioning
confidence: 99%